Analisis Strategi Pemasaran Produk Pembiayaan Murabahah - Indah Ayu Puspita Sari; Febriyanto; Durotun Nasikah (Universitas Muhammadiyah Metro, 2026)
The purpose of this research is to find out what the marketing strategy for Murabahah financing products is at BMT Assyafi'iyah Berkah Nasional and to find out what the SWOT analysis of the marketing strategy for Murabahah financing products is at BMT Assyafi'iyah Berkah National.This research method is descriptive qualitative: The technique used in collecting data for this research uses observation, interviews, documentation studies and focus group discussions. Then, in data analysis, descriptive analysis was carried out to identify marketing strategies for murabahah financing products at BMT Assyafliyah Berkah Nasional in Kotagajah based on SWOT analysis. The results of the research carried out are: 1) Marketing strategies, especially marketing of murabahah financing products implemented by BMT Assyafliyah Kotagajah, include several strategies, namely pick-up strategies, building networks, providing excellent service, and providing satisfactory facilities to increase customer trust and satisfaction, so that existing customers will not be separated from BMT. 2) The results of the SWOT analysis show that BMT Assyatliyah Kotagajah can compete in a competitive market. The results of the SWOT analysis are almost the same as BMT in general